Modern concepts regarding Meckel’s Diverticulum and its complications (Research, Society and Development, 2024)
Introduction: Meckel's diverticulum is a rare condition that arises from an abnormality in the embryonic process, resulting in an abdominal structure that can cause important clinical outcomes in patients. Objectives: The aim of this study was to evaluate the clinical, epidemiological and pathophysiological aspects of Meckel's diverticulum and its complications, building on knowledge based on case reports and knowledge based on the literature. Materials and Methods: This is an integrative literature review on the general clinical characteristics of Meckel's diverticulum and its complications. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Meckel's diverticulum”; “Complications”; “Propaedeutics” were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The articles showed that the occurrence of Meckel's diverticulum is more associated with males and pediatric patients. The pathophysiological mechanisms for its development were also discussed, as well as the main clinical manifestations and diagnostic forms. Conclusion: In this context, Meckel's diverticulum is, in most cases, a benign condition that presents with symptoms of acute abdomen and its varieties. The diagnosis is eminently clinical and complemented by imaging tests. Treatment includes analgesia to control the acute condition and surgical resection as the definitive therapeutic option.